Time-varying dependence research on wear of revolute joints and reliability evaluation of a lock mechanism. (February 2019) - Zhuang, Xinchen; Yu, Tianxiang; Shen, Linjie; Sun, Zhongchao; Guo, Bozhi
Abstract: The present study focuses on wear of revolute joints of a lock mechanism in an aircraft. A multibody dynamic model of the mechanism is built and validated by experiment. Experiment is also designed to obtain the wear coefficient, applying the wear coefficient as contact force and velocity dependent parameters in the wear processor. Wear simulation is carried out to acquire the samples of wear of each joint. As the dependence analysis requires dozens of samples, an adaptive extrapolation method is proposed to reduce time cost. Dependence analysis is conducted and the result shows that wear of each joint has strong dependence and the dependence is time-varying. The response surface method is used to build the relationship between the wear depth of the joints and the position deviation of the lock. The wear of the joints is described by Wiener process with drift parameter. D-vine Copula with time-varying parameter is used to construct the joint probability density function of wear of the revolute joints in the lock mechanism and reliability of the mechanism is evaluated. It shows that the time-varying dependence of wear of the joints has a significant influence on the reliability of the lock mechanism. Highlights: A multibody dynamic model of a lock mechanism is built and validated by experiment. Experiment is designed to obtain the wear coefficient of the materials, applying the wear coefficient as contact force and velocity dependent parameters in the wear processor. Adaptive extrapolation method is proposed to reduce time cost of wear simulation. Wear of the revolute joints in a mechanism is time-varying dependence The time-varying dependence of wear of the joints has a significant influence on the reliability of the lock mechanism